Cyfrowe przygotowanie przyszłych nauczycieli wczesnej edukacji do wdrażania koncepcji STEAM - Ziębakowska-Cecot, Katarzyna; Wieczorek, Paulina (Digital preparation of future early education teachers for implementing STEAM concepts, 2024)
In the face of rapid technological advancements, the significance of STEAM (Science, Technology, Engineering, Arts, Mathematics) education paradigms is increasing because it integrates the sciences with the arts, fostering creative thinking, problemsolving abilities, and technological competencies. There is a growing need to popularize the STEAM concept within the Polish education system to prepare students for the demands of the contemporary labour market. This necessitates digital and interpersonal skils from teachers, along with an awareness of the self-education need. The aim of this study was to assess the preparedness of future teachers of the “Preschool and Early School Pedagogy” specialization for STEAM-based education. The research was conducted in May 2024 using a survey technique among 103 fourth- and fifth-year students. The results indicate that future teachers are well-acquainted with popular educational tools and recognize the need to enhance their STEAM competencies. As many as 93% of respondents expressed interest in further training in this area. The study also revealed significant gaps in their education regarding STEAM. Teacher trainees demonstrated a willingness to implement STEAM concepts in their future teaching practices and a commitment to self-directed learning and competency development. The findings emphasize the necessity of updating and evaluating academic curricula and providing ongoing support to teachers in honing the skills essential for STEAM, thereby effectively preparing them for modern early childhood education.